2008
DOI: 10.1111/j.1865-1682.2008.01053.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Network Analysis Measures to Determine Potential Epidemic Size of Highly Contagious Exotic Diseases in Fragmented Monthly Networks of Dairy Cattle Movements in Ontario, Canada

Abstract: Adult milking cow movements occurring in monthly periods in 2004-2006 were analysed to compare three network analysis measures to determine the lower and upper bounds of potential maximal epidemic size in an unrestrained epidemic: the out-degree, the infection chain or output domain of a farm, and the size of the strong and weak components. The directed networks generated by the movements of adult milking cows were highly fragmented. When all the farms that were not involved in shipments were included in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
100
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(116 citation statements)
references
References 15 publications
9
100
1
3
Order By: Relevance
“…Although the GSC size may be an overestimate of a likely epidemic size40, it is useful information for determining the number of potentially exposed farms41. Again, enhancing surveillance and biosecurity at these premises is likely to have significant impact in terms of minimising the extent of a potential epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…Although the GSC size may be an overestimate of a likely epidemic size40, it is useful information for determining the number of potentially exposed farms41. Again, enhancing surveillance and biosecurity at these premises is likely to have significant impact in terms of minimising the extent of a potential epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the relative frequency of contact from each source production type was calculated for each of recipient production farm types for direct contact based on swine movement (Supplementary material, Table S1) and relative frequency of sharing among production types for indirect contact based on truck sharing (Supplementary material, Table S2) information. Then the contact rates assigned to a production type were adjusted by multiplying the relative frequency by the maximum out-degree for that production type (Supplementary material, Table S3), where maximum out-degree is the maximum number of unique outgoing contacts an individual or group has in the population (Dubé et al, 2008). This approach of using the maximum out-degree between farms is thought to lead to a more realistic epidemic size, as opposed to using either the total number of shipments or average out-degree, which will tend to overestimate or underestimate the epidemic size respectively (Dubé et al, 2008).…”
Section: Parametersmentioning
confidence: 99%
“…Then the contact rates assigned to a production type were adjusted by multiplying the relative frequency by the maximum out-degree for that production type (Supplementary material, Table S3), where maximum out-degree is the maximum number of unique outgoing contacts an individual or group has in the population (Dubé et al, 2008). This approach of using the maximum out-degree between farms is thought to lead to a more realistic epidemic size, as opposed to using either the total number of shipments or average out-degree, which will tend to overestimate or underestimate the epidemic size respectively (Dubé et al, 2008). Indirect contact rates (Supplementary material, Table S4) from the truck sharing contact matrix were based on the maximum number of farms sharing a single truck within one week.…”
Section: Parametersmentioning
confidence: 99%
“…Canada, Britain, Denmark, Sweden and some other countries' research results showed that livestock and poultry movement plays an important role in the spread of animal disease. The researchers also suggested that in the management of animal movements we should pay attention to the following points: 1) Mixed degree, which means the mixed level of directly infected animals and indirectly infected animals; 2) Dispersion degree, that is, one buys infected animals from another seller, then the infected animals involved in trading become scattered in the whole group of animals; 3) Complicated sources degree, namely, the buyer will buy animals from a number of sources [1][2][3][4][5][6][7][8]. However, the relevant research in China is scarce [9].…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce the risks for spread of disease in cattle movements, through describing the cattle markets and analyzing the risks in the process of cattle movements, this article wanted to provide the advice about the prevention of animal disease to farmers, practitioners and other related staffs in cattle movements and the reference to establish the disease spread mathematical model and dynamic model [3].…”
Section: Introductionmentioning
confidence: 99%